Problem-Based Teaching of Marketing Research and Students’ Living Conditions: An Example from A Polish University - Barbara MARCISZEWSKA (Communications of International Proceedings, 2023)
The motive behind the study and, consequently, the aim of this project is to show the possibility of engaging students in a cognitive process that leads to obtaining learning outcomes and implementing their work in research that leads to the acquisition of new knowledge. The importance of this study results from a gap in the literature, which, despite covering a multi-aspect discussion on "problem-based learning", does not address the students’ role in such a teaching process as co-creators and co-authors of research results; it is valuable to recognize they conduct research themselves as part of the teaching process. This research project used the methods: literature analysis, participant observation, and a survey - as an element of the teaching process while recognizing its role as a method for students to collect data from primary sources. The findings show that problem-based learning opens an opportunity for students to understand and emotionally feel the added value which is created by their own research work. It is an important way for improving self-esteem in the class and developing students’ research interests.
Keywords: problem-based learning; problem-based teaching; dual results; teaching outcomes; qualitative approach